Christian doctrine and the grammar of difference : a contribution to feminist systematic theology - McRandal, Janice (Emerging scholars., 2015)
McRandal argues that the doctrinal narrative of creation, fall, and redemption provides resources to resolve the theological impasse of difference in contemporary feminist theology. The divine economy reveals a God who enters into history and destabilizes fixed binaries and oppressive categories. As created subjects, we are sustained, affirmed, and drawn back into the Triune life, patterns present in liturgy, prayer, and practices of contemplation. The grammar of Christian faith cannot ultimately be uncovered except in prayer, opened beyond itself to a source of life and giving.